Psychometric evaluation of blood disaster management questionnaire-(floodDMQ-BM©) : confirmatory factor analysis and item response theory analysis - Mafauzy, Mohamad Masykurin (2020)
Background Flood disaster is the commonest natural disaster with a huge impact on health care services in Malaysia. Therefore, the FloodDMQ-BM© questionnaire is developed as a tool to assess the knowledge, attitude, and practice of health care providers regarding patient management during a flood disaster. This work aimed to further validate the FloodDMQ-BM© questionnaire by using Confirmatory Factor Analysis (CFA) and Item Response Theory (IRT) in order to confirm its validity in assessing the knowledge, attitude, and practice of health care providers regarding patient management during a flood disaster. Materials and Methods This observational cross-sectional study involved health care workers in the Emergency Department (ED) of Hospital Universiti Sains Malaysia (HUSM), Hospital Raja Perempuan Zainab II (HRPZ2), and Hospital Kuala Krai (HKK). The completed FloodDMQ-BM© questionnaire was analysed by using CFA and IRT to establish its validity and reliability. Result A total of 209 respondents participated in this study, yielding an 84% response rate. CFA method subjected on the attitude and practice components resulted in good factor loadings (>0.5) in nearly all items and good model fit indices values (CFI = 0.96-0.98, TLI = 0.95- 0.96, SRMR = 0.04-0.05, RMSEA = 0.07). Meanwhile, IRT analysis on the knowledge section showed a good two-way marginal fit based on S-X2, and a good model fit with RMSEA of 0.08. The items had good standardised loadings (>0.3) and marginal reliability of 0.651. Conclusion Our results confirmed that the FloodDMQ-BM© questionnaire displayed valid and reliable psychometric properties.